Emergency preparedness in South Africa: lessons from the Zimbabwean elections - Hernan del Valle; Tara Polzer (Forced Migration Review, 2003)
The presidential elections in Zimbabwe in May2002 took place within a context of political violence,economic crisis and increasing food shortages.As conditions deteriorated and the possibility of amass population exodus from Zimbabwe increased,neighbouring countries started preparations to dealwith the possibility of a mass influx of refugeesacross their borders.